Comparative Evaluation of Conventional and OnyxCeph (TM) Dental Software Measurements on Cephalometric Radiography - (:unkn) unknown (AVES, 2019)
Objective: Cephalometry can be measured with traditionally conventional analysing methods (hand tracing), as well as using computers. Many dental softwares have been developed for this purpose. The reliability of these programs are often compared with the conventional method. The aim of the present study was to compare the conventional method of manual cephalometric analysis with a computerized one, OnyxCeph (TM) (Image Instruments, Chemnitz, Germany) dental software. Methods: Lateral cephalometric radiographs of 150 patients (75 males and 75 females) age range 12-34 were traced by two methods. Conventional method and computerized (OnyxCeph) cephalometric analysis method. 2 maxillar, 3 mandibular, 2 maxillo-mandibular, 3 vertical, 7 dental and 1 soft tissue parameters; 10 angular, 8 linear totally 18 cephalometric parameters were measured. Intra-class correlation coefficients were performed for both methods to assess the reliability of the measurements. Results: The results 9 of 18 parameters were found statistically significant. They were Cd-A distance, Cd-Gn distance, Go-Me distance, GoGnSN angle, ANS-Me distance, upper incisor-NA distance, lower incisor-NB distance, lower incisor-NB angle, overbite distance. Conclusion: Despite some discrepancies in measured values between hand-tracing cephalometric analysis method and the OnyxCeph cephalometric analysis method, statistical differences were minimal and only Cd-A, Cd-Gn, Go-Me, ANS-Me, GoGnSN degrees were clinically important for cephalometric analysis OnyxCeph was evaluated as an efficient method to replace conventional method.
Keywords: Cephalometrics; manual tracing; onyxceph; computerized cephalometric program; reliability; LANDMARK IDENTIFICATION; REPRODUCIBILITY; RELIABILITY; CEPHALOGRAMS; ACCURACY; IMAGES; ERRORS; ANALOG; SPEED